SCHWARTZ APPLIANCE AND LIP BUMPER AS TREATMENT MODALITIES FOR MANDIBULAR CROWDING IN MIXED DENTITIONS - Chakar Kocevski, Stefana; Gavrilovikj, Irena; Nikolovski, Bruno (Journal of Morphological Sciences, 2023)
Dental crowding is the most common form of malocclusion. It is more pronounced in the mandible than in the maxilla and tends to increase with age. Depending on the degree of space deficiency and the age of the children the prevalence of dental crowding can be as high as 50%. Schwartz appliance and lip bumper have been widely used as an early treatment for increasing lower dental arch dimensions. The aim of this review is to evaluate the scientific research about the efficacy of Schwartz appliance and lip bumper and compare the changes caused by the two appliances in addressing mandibular crowding in the mixed dentition. A comprehensive literature search on the electronic databases: PubMed, Cochrane Library and Google Scholar was performed. Also, a search of the reference lists of included studies was conducted, to ensure comprehensive coverage of the literature. Search terms included "Schwartz appliance" OR "removable appliance" AND "lip bumper" OR "fixed appliance" AND "mandibular crowding" AND "mixed dentition" OR "early dentition". The search resulted in identifying several studies that met the inclusion criteria.Results show that both Schwartz appliance and lip bumper can effectively improve mandibular crowding in mixed dentition, although the extent and type of changes produced by these appliances may vary. Schwartz appliance is more effective in increasing inter canine width, while the lip bumper has more effect on increasing the arch length. Patient compliance as well as treatment duration are important factors that can have an effect on the success of orthodontic treatment. Schwartz appliance and lip bumper are effective in alleviating mandibular crowding, thus providing cost-effective and simple treatment in mixed dentition. The choice of the appliance should be based on the individual patientâ€™s needs and treatment goals. Further research is needed to evaluate and compare the stability and long-term effects of these two appliances as well as the need for further fixed orthodontic treatment. Key words: Schwartz appliance, lip bumper, mandibular crowding, mixed dentition   https://doi.org/10.55302/JMS2361169chk